Gothic vibrations and Edgar Allan Poe - Clarke, Frances (Horror Studies, 2016)
Abstract This is a study into vibrations – an element not often measured alongside literature – and how they can be seen featuring heavily within the tropes of Gothic fiction. Vibrations allow for research into the biological impacts of sounds and sensations upon the human body, which affect both the readers and characters of Gothic literature, and also a more in-depth understanding of what contributes to the discrepancy between the physical and the ethereal in these instances. In this article, these short stories by Edgar Allan Poe have been used as exceptional examples of highly vibrational Gothic texts: ‘The Masque of the Red Death’, ‘The Pit and the Pendulum’, and ‘The Tell-Tale Heart’. Researching vibrations invited a new approach towards these texts through the varying disciplines of science, music and philosophy. This allowed for a more distinct understanding of the reasons why this genre is capable of producing those thrilling sensations that Gothic readers seek.
https://katalog.adlr.link/Record/ai-49-aHR0cDovL2R4LmRvaS5vcmcvMTAuMTM4Ni9ob3N0LjcuMi4yMDVfMQ